Evaluation of etlingera elatior flower aqueous extract (EEAE) as treatment of colon cancer in rat model (pilot study) - Shuang, Wee Lu (Universiti Sains Malaysia, 2025)
Colon cancer is a type of cancer that occurs in the colon or rectum. Therefore, sometimes it is also known as colorectal cancer (CRC). It is a leading cause of cancer-related deaths worldwide, even though there are available treatments for colon cancer, undesirable side effects often accompany it. Etlingera elatior, known as bunga kantan in Malaysia, is a traditional medicinal plant with high potential therapeutic effects with excellent antimicrobial, antioxidant, anticancer, antidiabetic, anti-inflammation, and anti-ageing properties. However, limited scientific research has been conducted on its antitumour effects against colon cancer. Therefore, this study investigates the in vivo antitumour effects of E. elatior flower aqueous extract (EEAE). EEAE is extracted using the sonication method. Toxicological assessment was performed using the brine shrimp lethality assay (BSLA) with a series of concentrations including concentrations of 10 mg/ml, 1 mg/ml, 3 mg/ml, 300 μg/ml, 100 μg/ml, 30 μg/ml, and 10 μg/ml. The LC50 of EEAE determined after the 24-hour incubation period was 2286 ppm (μg/ml), classifying EEAE as non-toxic based on Meyer and Clarkson toxicity standards. The antitumour efficacy of EEAE was further evaluated in an Azoxymethane-induced colon cancer model using male Sprague-Dawley rats. Histological analysis with Hematoxylin and Eosin (H&E) and Masson-Trichrome (MT) staining demonstrated substantial improvements in colon morphology upon treatment with EEAE. These findings suggest that EEAE is a promising natural product with antitumour properties against colon cancer, with no observed toxicity in vivo. Further research is warranted to explore its therapeutic potential and underlying mechanisms